TANGGUNG JAWAB AGEN PERJALANAN WISATA ATAS KELALAIAN PIHAK REKANAN DALAM MENJALANKAN PAKET PERJALANAN WISATA - Harianto, Dedi; Andrianti, Syarifah Lisa; Panggabean, Artha Priscilia Margareth (Fakultas Hukum Universitas Sriwijaya, 2025)
A travel agent is a part of a company whose business activities are planning, organizing and selling various types of travel packages. Tourist travel agents have cooperation agreements with partners as an agreement that creates rights and obligations for the parties. It is still common that the facilities received by tourists as consumers are not in accordance with what has been promised by partners when carrying out tour packages. Considering this, the issue discussed is how to regulate legal relations between PT. Bintan Medan Tourism Holidays with partners in organizing tour packages, whether PT. Bintan Medan Tourism Holidays can be held responsible for the partner's negligence in organizing the tour package, what is the mechanism for resolving problems at PT. Bintan Holiday Tour if there is negligence on the part of the partner in organizing the tour package. The research method used is normative juridical research which refers to legal norms which is carried out by means of literature study in order to obtain secondary data in the form of primary, secondary and tertiary legal materials related to the problems studied. This research has a descriptive nature. Writing research through regulations and legal materials related to this writing, in research conducting field studies at PT. Bintan Medan Tourism Vacation, the data analysis method used is a qualitative method obtained from the results of interviews with PT. Bintan Medan Tourism Holidays. The research results found that there was negligence on the part of partners in carrying out tour packages. PT. Bintan Medan Tourism Holidays receives compensation for products or services if there are consumers who suffer losses due to negligence by partners. The partner party will be fully responsible for all forms of losses in accordance with the provisions and will be settled outside of court in accordance with what has been agreed.